Metode Penilaian Kondisi Perusahaan dan Harga Saham melalui Analisis Fundamental Berbasis Rasio Keuangan - Pratama, Yhordana Cahya; Huda, Miftahul; Astari, Yeni; Salsabila, Alfi Rahma; Zahrah, Siti (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study aims to evaluate stock prices using fundamental analysis based on financial ratios in companies that have been listed on the stock exchange. This analysis plays an important role in increasing investor and creditor confidence in the company and helps determine the value of shares accurately. The research was conducted using the substitution method and literature study. Financial ratio-based fundamental analysis provides a comprehensive picture of the company's financial performance. Ratios such as Net Profit Margin, Return on Investment (ROI), Return on Equity (ROE), and Debt to Equity Ratio (DER) were analyzed to assess operational efficiency and profitability. The results show that companies with Net Profit Margin above 20%, ROI of at least 30%, and ROE above 40% are performing well, reflecting the ability to generate significant profits and pay dividends. High asset and inventory turnover ratios reflect efficient management, while DER below 50% indicates optimal use of debt. This study also highlights the importance of Earning per Share (EPS) and Price to Earning Ratio (PER) in determining stock value, and recommends investors to consider these ratios in making investment decisions.